2015
DOI: 10.1080/17439884.2015.1064952
|View full text |Cite
|
Sign up to set email alerts
|

Using Facebook as a co-learning community in higher education

Abstract: Students' cultural capital plays a major role in their success in higher education. In Sweden today, many students come from diverse cultural, social and educational backgrounds. Knowledge of requirements in academic systems differs widely. Some students feel insecure about how to interpret academic codes, thus weakening these students' opportunities for academic success. The major goal of this project was to lay the groundwork for a more equal educational system. Using social media, in this case conversations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 12 publications
1
33
0
4
Order By: Relevance
“…For example, in their study of 24 students participating in a closed Facebook forum, Cuesta et al (2015) found that forum participation enhances the understanding of academic culture and knowledge production of higher education students from diverse backgrounds. Ratneswary and Rasiah (2014) highlight Facebook's capacity to enhance teaching and learning in team-based environments by providing innovative ways of involving and motivating students.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in their study of 24 students participating in a closed Facebook forum, Cuesta et al (2015) found that forum participation enhances the understanding of academic culture and knowledge production of higher education students from diverse backgrounds. Ratneswary and Rasiah (2014) highlight Facebook's capacity to enhance teaching and learning in team-based environments by providing innovative ways of involving and motivating students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Not surprisingly given its popularity, much research attention has been paid to Facebook (Cuesta, Eklund, Rydin, & Witt, 2015;Irwin et al, 2012;Kabilan, 2016;Madge, Meek, Wellens, & Hooley, 2009;Ratneswary & Rasiah, 2014;Santos & Cuta, 2015;Vivian, Barnes, Geer, & Wood, 2014). Manca and Ranieri (2013) conducted a literature review of 23 peer-reviewed articles focusing on Facebook as a learning environment to explore "the extent to which its pedagogical potential is translated into practice" (p. 487), explicating three themes: instructional efficacy; supportive and interactive learning tool; and students' reactions to Facebook as an instructional tool.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Administrators can select settings that allow members to post directly to the group page. These combined set of features make Facebook groups an enticing option for those in higher education who wish to engage and foster interaction among a specific network of students (e.g., Bowman & Akcaoglu, 2014;Cuesta, Eklund, Rydin, & Witt, 2015).…”
Section: Groupsmentioning
confidence: 99%
“…(Sørensen, 2017, s. 1) I international kontekst er der som Sørensen (2017) diskuterer divergerende syn på studerendes inkorporering af sociale medier i relation til deres studiepraksis. Mens nogle fremhaever fx Facebook, som meningsfuldt og relevant i de studerendes studiepraksisser (Aaen & Dalsgaard, 2016;Cuesta et al, 2015;McEwan, 2011), naerer andre bekymringer omkring sociale mediers egnethed i relation til uddannelse (Kirschner, 2015, Friesen & Lowe, 2012. Generelt synes der dog at vaere enighed om, at ideen om de studerende som selvdrevne og saerdeles kompetente digitale indfødte er problematisk og ensidig.…”
Section: Studerendes Brug Af Digitale Teknologier I Uddannelseunclassified